Manipulating the interactions between the lipid bilayer and triblock Janus nanoparticles: insight from dissipative particle dynamics. Issue 2 (22nd January 2021) - Li, Jiawei; Wang, Junfeng; Yan, Youguo; Li, Zhen; Zhang, Jun
Abstract : The interplay between triblock Janus nanoparticles and the lipid bilayer can be controlled by regulating the arrangement of hydrophobic– hydrophilic patches in triblock Janus nanoparticles. Abstract : Triblock Janus nanoparticles (TJPs) have demonstrated unique physical properties that make them beneficial for versatile biomedical applications, but there is a lack of understanding on the effect of hydrophobic–hydrophilic patch arrangement on TJP–bilayer interactions. Here, by adopting dissipative particle dynamics simulations, the interplay between the bilayer and TJPs with different hydrophobic–hydrophilic patches is systematically studied. By scrutinizing the complete transmembrane process of different TJPs, we reveal that the hydrophobic–hydrophilic patch arrangement of TJPs significantly affects the internalization pathway of TJPs, as well as the dynamic behaviors and stability of internalized TJPs. The TJPs with hydrophilic patches on two poles are more stable within the bilayer but their internalization process is more time-consuming. The TJPs with hydrophilic patches on two poles possess better penetration capability across the lipid bilayer due to their metastable configuration within the bilayer. Meanwhile, the ratio of hydrophobic–hydrophilic patches of TJPs is a secondary factor influencing the TJP–bilayer interactions. These findings demonstrate that the interactions between TJPs and the bilayer can be regulated by manipulating the hydrophobic–hydrophilic patch arrangement of TJPs, which provide valuable information for designing hybrid nanocomposites and facilitate the potential application of TJPs.